A comparative study of values among Chinese and U.S. entrepreneurs: Pragmatic convergence between contrasting cultures - Holt, David H. (Journal of Business Venturing, 1997)
The People's Republic of China is the world's leading Communist power, yet it also represents the largest potential market for international investment and development. In recent years, China has actively pursued private enterprise development, passing its first Private Company Act in 1988, and subsequently encouraging entrepreneurial activities. More than a half-million new ventures in high-growth manufacturing, engineering, and infrastructural development have been independently established in China in little more than six years, and although it would be presumptuous to assume that China is racing toward a free enterprise economy, there are major changes taking place. From an entrepreneurial perspective, these changes are in sharp contrast to the nation's political ideology, and those who are pursuing new ventures constitute a vanguard of individuals at odds with a majority of society. A critical concern is whether China's entrepreneurs pose a threat to those who are entrenched in a political ideology that, by definition, is opposed to free market economics and private enterprise. As Hofstede (1980) has pointed out, characteristics of a people are defined by their prevailing value systems, and research by Bond (1991), Hofstede (1983a, 1983b), Schwartz (1992), and Triandis et al. (1986) has shown that by systematically studying human values we can gain valuable insights about patterns of behavior, motivation, and expectations of cross-cultural boundaries. Consequently, this study was developed to replicate previous value-related studies among Chinese entrepreneurs and nonentrepreneurial managers. A sample of more than 200 executives of state-owned and privately founded industrial companies provided comparable groups for comprehensive interviews. An analogous sample of U.S. entrepreneurs was selected to represent Western values. This extends several previous studies on private enterprise development in China, but, clearly, the convenient and limited sample cannot be construed as representative of a geographically and ethnically diversified country of more than 1.1 billion people. However, it does provide useful insights to differences and similarities in work-related values between Chinese entrepreneurs, managers, and U.S. entrepreneurs as exploratory research. A primary consideration of this study was to enrich the existing research concerning entrepreneurial values, and in the process, question whether Chinese entrepreneurial values are similar to those held by U.S. entrepreneurs. If so, there would be a stronger case for convergence of value systems and commensurate behavior. Similarities would also support arguments by many that entrepreneurial characteristics, such as individualism, achievement motives, and self-deterministic behavior, are universal. This is complicated, however, by a Confucian social philosophy that places little value on these attributes while underscoring the importance of collective behavior, conformist behavior, and referent group loyalty. It is further complicated by two generations of Communist doctrine that has suppressed individual initiative, commercial achievement, and social mobility. Can entrepreneurial values prevail under such adverse conditions? More specifically, can values associated with individualism and self-determination exist in a society that is collectivist and conformist? Several recent studies on entrepreneurial values suggest that apparent contradictory value sets might co-exist (Baum et al. 1993; Chow and Tsang 1994; Erez and Earley 1993; Hofstede and Bond 1988; Holt, Ralston, and Terpstra 1994). Entrepreneurial research has also questioned the concept of universal values and found that, in many instances, cultural-based values are not necessarily malleable (McGrath et al. 1992), values are often contingent on prevailing cultural antecedents (Shenkar and Von Glinow 1994), and discordant or paradoxical values exist within so-called collectivist societies, among presumed cohesive groups, and within well-defined ethnic clusters (McGrath, MacMillan, and Scheinberg 1992; Ohe, Honjo, and MacMillan 1990; Ralston et al. 1994; Triandis et al. 1988). The current study revealed patterns of value orientations among Chinese entrepreneurs, Chinese executives of state-owned or joint venture firms, and U.S. entrepreneurs that in some instances were substantially different, and in other instances quite similar. Contrasts in these patterns suggest an apparent paradox of entrepreneurship in a collectivist society like China, and in particular, a potential confrontation between Chinese entrepreneurs and nonentrepreneurial managers. The results showed that, indeed, the respondent Chinese managers and entrepreneurs differed sharply on many crucial value dimensions, and although the survey was limited to a southern industrial province, there is the possibility that China may be facing an extremely difficult transition period toward a constrained market economy with overtones of a possible ideological backlash. The results revealed many similarities between the respondent Chinese and U.S. entrepreneurs, but also several important differences steeped in Confucian social philosophy. Although there may be some convergence in values, it is more likely that Chinese entrepreneurs are simply pragmatic, and therefore selective in developing behavior that reflects values associated with achievement, independence, freedom of choice, and self-determination. If these results could be interpreted as prevalent beyond our exploratory sample, then pragmatic expectations may be driving private enterprise development in China more than cultural values, but this is difficult to verify. Whatever implications are drawn from this study must also be taken cautiously because there are indications that definitions of certain values, such as achievement or independence, may have substantially different meanings to American and Chinese entrepreneurs. Care was taken to make translations comparable during the field interviews, but Western concepts inherent in the instruments used for value research may have elicited responses or associated meanings among the Chinese that cannot be accurately interpreted.